Fundamentals of Piano Pedagogy Fuelling Authentic Student Musicians from the Beginning - Thompson, Merlin B. (SpringerBriefs in Education,, 2018)
How can piano teachers successfully foster student participation and growth from the outset? How can teachers prepare and sustain their influential work with beginner student musicians? This book presents answers to these questions by making important connections with current music education research, masters of the performance world, music philosophers, and the author's 30-year career as a piano pedagogy instructor in Canada, the USA, Australia, New Zealand, and Japan. It investigates the multilayered role piano teachers play right from the very beginning - the formative first four to five years during which teachers empower students to explore and expand their own emerging musical foundations. This book offers a humane, emancipatory, and generous approach to teaching by grappling with some of the most fundamental issues behind and consequences of studio music teaching. More experiential than abstract and cerebral, it demonstrates how teaching beginner piano students involves an attentiveness to musical concerns like our connection to music, learning to play by ear and by reading, caring for music, the importance of tone and technique, and helping students develop fluency through their accumulated repertoire. Teaching beginner students also draws on personal aspects like independence and authenticity, the moral and ethical dignity associated with democratic relationships, and meaningful conversations with parents. Further, another layer of teaching beginners acknowledges both sides of the coin in terms of growth and rest, teaching what is and what might be, as well as supporting and challenging student development. In this view, how teachers fuel authentic student musicians from the beginning is intimately connected to the knowledge, beliefs, and values that permeate their thoughts and actions in everyday life. Fundamentals of Piano Pedagogy stands out as a much-needed instructional resource with immense personal, practical, social, philosophical, educational, and cultural relevance for today's studio music teachers. Its humanistic and holistic approach invites teachers to consider not only who they are and what music means to them, but also what they have yet to imagine about themselves, about music, their students, and life. .